A literature review of the role of spirituality in health, health care, diseases, social conditions, general well-being and health education programs during the last three decades - Metz, Christina A. (My University, 1998)
This project presents an extensive literature review of the construct of spirituality in health, health care, disease and social conditions, general well-being, and health education programs during the last three decades. The findings support research that health care needs to take on a holistic approach, to include the mind, body and spirit in regards to treatment and education. The present study concluded that health is a dynamic process and must include the spiritual dimension. Attending places of worship have a positive influence on health and a negative influence on disease. Spiritual factors are also important in the prevention and treatment of disease. Spirituality and certain organized religious practices have a positive influence on life satisfaction, subjective wel1-being, and social conditions. Since spirituality has a positive affect / influence on health and health outcomes, health educators should incorporate the spiritual dimension into health education programs. Examples of successful application of spirituality showing positive results within health education programs are also included in this research paper.
Keywords: Spirituality -- Health aspects.; Health -- Religious aspects.